Edukacja i film – punkty styczne. Refleksja o filmie w edukacji i w badaniach edukacyjnych - Zamojska, Eva (Kultura-Społeczeństwo-Edukacja, 2016)
The paper reflects on the use of film in education and in education research. The author sets out to answer questions on legitimization and specific nature of pedagogical interpretation of films and audiovisual materials. She searches for answers to these questions in two ways: on the one hand, by broadening the research field in connection with a constructivist methodology and using interpretive approaches in social sciences and humanities; on the other hand, by following the postulates of contemporary pedagogy promoting empowering students in the education process.